#Insta personality: Personality expression in Instagram accounts, impression formation, and accuracy of personality judgments at zero acquaintance. Issue 3 (3rd August 2022) - Osterholz, Sarah; Mosel, Emily I.; Egloff, Boris
Abstract: Objective: This study examined personality expression, impression formation, and the consensus and accuracy of zero‐acquaintance personality judgments that were based on people's Instagram accounts. Method: Self‐ and informant reports of the Big Five personality traits, self‐esteem, and narcissism were collected for 102 Instagram users. Screenshots were taken of Instagram users' profiles, including up to the 102 latest available Instagram posts. A number of Instagram cues were objectively retrieved, counted, and rated by independent trained cue coders from the screenshots. 100 unacquainted observers then judged the Big Five traits, self‐esteem, and narcissism on the basis of Instagram screenshots only. Results: We identified Instagram account characteristics that were associated with users' personality traits (measured with self‐reports, informant reports, and self‐informant composites) and observers' zero‐acquaintance personality judgments. Personality judgments that were based on Instagram accounts demonstrated consensus and significantly converged with Instagram users' Big Five traits, self‐esteem, and narcissism across all three personality criteria. Averaged‐observer accuracy correlations for self‐informant composite scores ranged from r  = .44 ( p  < .001) for extraversion to r  = .25 ( p  = .013) for conscientiousness. Conclusions: Our findings provide insight into cue processes of online self‐portrayal and impression formation on Instagram and the level of zero‐acquaintance accuracy.